A REVIEW OF THE FACTORS OF ANXIETY IN SPEAKING ARABIC LANGUAGE AND THE 4TH INDUSTRIAL REVOLUTION - Mohamed Mokhtar, Mohd Ieruwan; Che Haron, Sueraya (Journal of Islamic Educational Research, 2020)
The Fourth Industrial Revolution (4th IR) influences educational institutions through the transformation process in delivering knowledge among the students. It also affects the process of learning a language such as the Arabic Language as a foreign language. Speaking skill is a productive skill in learning the language, which is the highest skill in applying the language. The study of foreign language anxiety has attracted much attention in the field of foreign language education in the past few decades. Thus, many causal factors influence Arabic language learning which contributes to anxiety in speaking the language among the students. The paper aims to review and identify the factors that contribute to anxiety in speaking skill during the 4th IR era, especially in the process of learning Arabic. The methodology uses in the study is library research which involves recent sources such as books, magazines, seminars, conferences, sources from the internet, articles and journals related to the study. The discussion shows that many factors contribute to the emergent of anxiety among the students. Ultimately, it aims to encourage educators to find the initiatives in addressing anxiety issue faced by students during the 4th IR while teaching Arabic Language.